Divine Intervention In Naqli Cognition Shackles; The Prominent Promised Emissaries’ Disclosure - Kirembwe Rashid Abdul Hamed; Mohd Aderi Che Noh; Siti Rosilawati Ramlan; Mohammad Najib Jaffar; Sakinah Ahmad; Hayati binti Ismail; Hayati Ismail; Maziahtusima Ishak; Mardhiah Yahaya; Sarifah Nurhanum Syed Sahuri (Tazkiyyah Global, 2025)
Non-Indexed Publication